Investigation of thermal conductivity and related parameters of early-age cement paste. (July 2020) - Zhao, Haitao; Fan, Guangchao; Wei, Zhenzhong; Wang, Jian; Huang, Donghui
Highlights: The thermal conductivity of early-age cement paste changed obviously with age. A multiscale thermal conductivity prediction model of early-age cement paste was proposed. An improved inversion program was developed based on particle swarm optimization. The thermal conductivity of each phase and parameters of thermal resistance in cement paste were obtained. Abstract: Thermal conductivity (TC) of cement-based materials is a key parameter for temperature field analysis and crack control at early age. In this study, the TC of early-age cement paste was experimentally determined by the parallel hot wire technique. The test results showed that the TC of early-age cement paste changed obviously with age and water to cement ratio ( w/c ). The TC curves of cement pastes with different w/c were similar and could be divided into three stages, i.e., the curves first rapidly decreased, then sharply increased, and finally tended to stabilize. The TC of the cement paste almost linearly decreased with w/c after 40 hours. Meanwhile, based on a combined generalized self-consistent method with CEMHYD3D, an effective TC multiscale predictive model for early-age cement paste was proposed considering the thermal resistance. An improved inversion program was simultaneously developed based on the particle swarm optimization. The TC of each phase in cement paste and the parameters of thermal resistance were obtained using the inversion program with experimental data. The inversion results showed that the deviations of the TC of each phase and the parameters of thermal resistance with different w/c were minimal and that the algorithm of the inversion program proposed was robust. The TC multiscale model predictive curves were in good agreement with the test data and the predictive capability of the TC multiscale model for cement paste was successfully validated.